Y-chromosome diversity of the three major ethno-linguistic groups in the Republic of North Macedonia - Jankova, Renata; Seidel, Maria; Videtič Paska, Alja; Willuweit, Sascha; Roewer, Lutz (Elsevier BV, 2019)
A total of 314 individuals representing the three major ethno-linguistic groups (ethnic Macedonians, Albanians and Turks) in the Republic of North Macedonia were analyzed for Y-SNPs and Y-STRs using minisequencing and fragment analysis. The haplogroup composition differed remarkably between the three groups with dominance of haplogroup I2 in ethnic Macedonians (28.1%), E1b in Albanians (35.3%) and J2a (34.9%) in Turks, respectively. The haplotype analysis using the YFilerPlus kit disclosed a significant reduction in diversity values (DC, GD) for the Turkish subgroup compared to the Macedonian and Albanian speaking populations. The Y-STR based population analysis revealed a similarity of ethnic Macedonians with neighboring Serbians and Bulgarians. The same holds true for the Albanian speakers from Macedonia and Albania, whereas the Turkish minority in North Macedonia stands apart from the population in Turkey.
Keywords: Y-SNP; Y-STR; Haplogroup; Haplotype; YHRD; Macedonians; Albanians; Turks